The Influence of Accrual Accounting Usage on Sustainable Development Goals (SDG) through Maqasid Shariah - Rosnia Masruki; Mustafa Mohd Hanefah (Universitas Darussalam Gontor, 2024)
This study aims to explore the influence of accrual information usage on achieving Sustainable Development Goals (SDG) in accordance with maqasid shariah. Conducted qualitatively, it involved interviews with accountants from Malaysian Ministries and Local Authorities (PBT), followed by thematic analysis. The findings reveal that utilising accrual information in these entities significantly influences strategies related to SDG and maqasid shariah principles. The varied benefits indirectly contribute to SDG attainment, aligning with Malaysia MADANI's overarching policy framework, embracing six core principles: sustainability, care and compassion, respect, innovation, prosperity, and trust. This study recommends regular comprehensive reporting rooted in SDGs and maqasid shariah, highlighting its relevance. Moreover, it emphasises how accrual information usage shapes the implementation of SDG strategies in line with maqasid shariah, supporting the national government framework.